2013
DOI: 10.1039/c3dt51531a
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical assembly of discrete copper(ii) metallo-structures from pre-assembled dinuclear (bis-β-diketonato)metallocycles and flexible difunctional co-ligands

Abstract: The sequential interaction of preformed [Cu 2 (L 1 ) 2 (THF) 2 ] (where H 2 L 1 is 1,1-(1,3-phenylene)-bis(4,4-dimethylpentane-1,3-dione incorporating a 1,3-phenylene linker between its two β-diketone domains) and [Cu 2 (L 4 ) 2 ]·2H 2 O (where H 2 L 4 is 1,1-(4,4'-oxybiphenylene)-bis(4,4-dimethylpentane-1,3-dione) incorporating a flexible oxybiphenylene linkage between the two β-diketone groups) with the potentially difunctional aliphatic non-planar co-ligands, N-methylpiperazine (mpip), N,N'-dimethylpiperazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Even if the crucial aspect of qubits entanglement has not been addressed in this work it can be easily achieved through connection of β-diketonate pockets in more complex architectures. 58 , 59 This approach has already been successfully employed to couple different spin centers 60 and to address them individually in resonance experiments in particular in lanthanide polynuclear complexes thanks to their significantly different g -factors. 61 …”
Section: Discussionmentioning
confidence: 99%
“…Even if the crucial aspect of qubits entanglement has not been addressed in this work it can be easily achieved through connection of β-diketonate pockets in more complex architectures. 58 , 59 This approach has already been successfully employed to couple different spin centers 60 and to address them individually in resonance experiments in particular in lanthanide polynuclear complexes thanks to their significantly different g -factors. 61 …”
Section: Discussionmentioning
confidence: 99%
“…The copper atoms bridged by a piperazine unit are separated by 6.7477(6) Å. The structure of 3 differs markedly from that of [{Cu 2 L 2 } 2 (1‐methylpiperazine) 2 ]⋅2(1‐methylpiperazine) (R= t Bu) ( 4 ) reported previously, which is a discrete dinuclear species with 5‐coordinate copper(II) centres to which axial 1‐methylpiperazine coligands are bound on opposite sides of the Cu 2 (L) 2 coordination plane via their secondary N‐donors (Figure S4); this product was synthesized employing different conditions from those used for 3 .…”
Section: Figurementioning
confidence: 80%
“…Cu II complexes [Cu 2 L 2 (solvent) n ], incorporating dinuclear “platforms” of type 1 , interact with a variety of heterocyclic nitrogen ligands to form both discrete and framework structures containing either 5‐ or 6‐coordinate copper ions . For example, recrystallization of previously reported [Cu 2 L 2 (THF) 2 ] (Cu 2 L 2 = 1 ; R= t Bu) from N ‐methylmorpholine resulted in the discrete binuclear complex, [Cu 2 L 2 ( N ‐methylmorpholine) 2 ] . We have investigated the effect of pressure on this product by X‐ray diffraction with the aid of a diamond anvil cell (DAC) .…”
Section: Figurementioning
confidence: 99%
“…Lu et al [8] reported the first example of a 2D poly-pseudo-rotaxane developed starting from a discrete stool-like metallocycle. Metallorings, based on transition metals capable of expanding their coordination, can be used as platforms to hierarchically assemble extended metallo-supramolecular systems [12][13][14][15] as demonstrated by Lindoy et al This strategy has also allowed to isolate a 1D polyrotaxane, where a copper-based metallocycle and a pyridyl bridging ligand self-assemble to form a 1D coordination polymer (the axle) and a discrete rectangular box (the stopper) [10].…”
Section: Introductionmentioning
confidence: 99%
“…pyridyl bridging ligand self-assemble to form a 1D coordination polymer (the axle) and a discrete rectangular box (the stopper) [10]. In order to design metallocycles bearing metal ions that can change their coordination sphere by ligand substitution or by expanding the coordination number, 2+ charged metal ions and bis-βdiketone ligands have been proven to be ideal building blocks [12][13][14][15]. For instance, we have previously demonstrated that Cu(II) and a bis-β-diketone can be used to self-assemble a constitutional dynamic library of metallocycles [16], where the interactions with σ-donor guests via Cu-N bonds drive the system toward a triangular metallobox [17,18] that can be used also to catalyze host reactions [19].…”
Section: Introductionmentioning
confidence: 99%